Validity of Structured Assignment Sheet to Train Argumentation Skills on Buffer Solution - Arza Rizky Septi Ansyach; Suyono Suyono (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The purpose of this study was to produce structured task sheets to practice argumentation skills on buffer solution material. This research is a development research to produce products with the ADDIE development model which is limited to the design and development analysis stage. The developed structured assignment sheet contains enriched questions to practice argumentation skills on buffer solution material. The data obtained in this study is the feasibility of the validity aspect. The instruments used to obtain content and construct validity data were validation sheets assessed by three validators. Learning devices are declared to meet the validity criteria (based on content and construct) if they get a minimum rating mode (Mo) of 4 (valid) from the range 1 to 5 on a Likert scale. The results showed that according to the assessment component, both content and construct validity got an assessment mode (Mo) of 5 (very valid). The developed structured task sheets are declared valid to train argumentation skills.